[OP.6A.07] SLEEP DISORDERED BREATHING IS ASSOCIATED WITH BLOOD PRESSURE AND CAROTID ARTERIAL STIFFNESS IN A SAMPLE OF OBESE CHILDREN. (September 2016) - Tagetti, A.; Bonafini, S.; Zaffanello, M.; Cavarzere, P.; Dalle Vedove, F.; Maffeis, C.; Antoniazzi, F.; Fava, C.
Abstract : Objective: Sleep disordered breathing (SDB) and high blood pressure (BP) are more frequent among obese with respect to normal weight children and this may be due to endothelial dysfunction and a worsened arterial stiffness. The aim of this study was to evaluate the possible association between SDB and BP and the possible role of endothelial function and local and systemic arterial stiffness in a sample of obese children asymptomatic for sleep disturbances. Design and method: Thirty-nine obese children were included in the study. Children underwent overnight limited channel polysomnography; vascular measurements included: (i) office and 24-hour ambulatory BP, (ii) brachial flow-mediated dilatation (FMD), carotid intima media thickness (cIMT), and distensibility (DC) by ultrasounds and (iii) systemic arterial stiffness (SI) by digital volume pulse analysis. Results: Significant correlations between different BP measurements (both office and ABPM estimated by z-score) and SDB were found, including respiratory disturbance index (RDI), apnea-hypopnea index (AHI), the number of desaturation/h, mean peripheral saturation (r ranging between 0.330 to 0.474). Carotid distensibility (DC) correlated with AHI (r = −0.367; p = 0.030) and with mean oxygen saturation (r = 0.401; p = 0.017). To the contrary, no relation between either FMD or SI or cIMT and all the tested respiratory markers was found. In multivariate analysis, supine z-SBP remained independently associated with the number of desaturation per hour or AHI also after correction for DC and BMI. Figure. No caption available. Conclusions: Conclusions: Our data suggest that in obese children, even if asymptomatic for sleep respiratory problems, SDB might worsen BP, in part through an increase in arterial stiffness.